Supervised learning events in the Foundation Programme: a UK-wide narrative interview study. Issue 10 (16th October 2014) - Rees, Charlotte E; Cleland, Jennifer A; Dennis, Ashley; Kelly, Narcie; Mattick, Karen; Monrouxe, Lynn V
Abstract : Objectives: To explore Foundation trainees' and trainers' understandings and experiences of supervised learning events (SLEs), compared with workplace-based assessments (WPBAs), and their suggestions for developing SLEs. Design: A narrative interview study based on 55 individual and 19 group interviews. Setting: UK-wide study across three sites in England, Scotland and Wales. Participants: Using maximum-variation sampling, 70 Foundation trainees and 40 trainers were recruited, shared their understandings and experiences of SLEs/WPBAs and made recommendations for future practice. Methods: Data were analysed using thematic and discourse analysis and narrative analysis of one exemplar personal incident narrative. Results: While participants volunteered understandings of SLEs as learning and assessment, they typically volunteered understandings of WPBAs as assessment. Trainers seemed more likely to describe SLEs as assessment and a 'safety net' to protect patients than trainees. We identified 333 personal incident narratives in our data (221 SLEs; 72 WPBAs). There was perceived variability in the conduct of SLEs/WPBAs in terms of their initiation, tools used, feedback and finalisation. Numerous factors at individual, interpersonal, cultural and technological levels were thought to facilitate/hinder learning. SLE narratives were more likely to be evaluated positively than WPBA narratives overall and by trainees specifically. Participants made sense of their experiences, emotions, identities and relationships through their narratives. They provided numerous suggestions for improving SLEs at individual, interpersonal, cultural and technological levels. Conclusions: Our findings provide tentative support for the shift to formative learning with the introduction of SLEs, albeit raising concerns around trainees' and trainers' understandings about SLEs. We identify five key educational recommendations from our study. Additional research is now needed to explore further the complexities around SLEs within workplace learning.